Degradation of austenite stainless steel by atmospheric exposure in tropical marine environment. (May 2013) - Luo, H; Li, X G; Dong, C F; Xiao, K
Abstract : The atmospheric corrosion kinetics of AISI 304 and AISI 316 stainless steel in tropical marine environments is observed by weight loss. The corrosion products are identified by laser Raman spectroscopy, and surface morphology is observed by SEM. The results show that the corrosion rates tend to decrease as the exposure time increases. The mass loss obeys the empirical kinetics equation. The value of n can be used to predict the corrosion resistance of stainless steel, indirectly. The rust layer composition of the two stainless steels is different, and the percentage of Fe3 O4 and β -FeOOH are also different.